Evolution in the Treatment of Psychiatric Disorders: From Psychosurgery to Psychopharmacology to Neuromodulation - Staudt, Michael D.; Herring, Eric Z.; Gao, Keming; Miller, Jonathan P.; Sweet, Jennifer A. (Frontiers in Neuroscience, 2019)
The treatment of psychiatric patients presents significant challenges to the clinical community, and a multidisciplinary approach to diagnosis and management is essential to facilitate optimal care. At times, these treatments have involved mystical, medical and surgical approaches, and developments in the field have sparked the interest of psychiatrists, psychologists, and neurosurgeons, among others. In particular, the neurosurgical treatment of psychiatric disorders, or “psychosurgery”, has held fascination throughout human history as a potential method of influencing behavior and consciousness. Early evidence of such procedures can be traced to prehistory, and interest flourished in the nineteenth and early twentieth century with greater insight into cerebral functional and anatomic localization. However, any discussion of psychosurgery invariably invokes controversy, as the widespread and indiscriminate use of the transorbital lobotomy in the mid-twentieth century resulted in profound ethical ramifications that persist to this day. The concurrent development of effective psychopharmacological treatments, including lithium and chlorpromazine virtually eliminated the need and desire for psychosurgical procedures, and accordingly the research and practice of psychosurgery was dormant, but not forgotten. The evolution in the treatment of psychiatric disorders from historical to modern practice is intimately connected with developments in behavioral neuroscience, neuroimaging, psychopharmacology, and neurosurgery. With the fall of ablative surgery came the rise of psychopharmacology, although the high rates of treatment resistance or failure necessitate alternative strategies. There has been a recent resurgence in interest for non-ablative surgery for psychiatric disorders, due in part to modern advances in functional and structural neuroimaging and neuromodulation technology. In particular, deep brain stimulation is a promising treatment paradigm with the potential to modulate abnormal pathways and networks implicated in psychiatric disease states. Although there is enthusiasm regarding this resurgence in surgical treatments, it is important to reflect on the scientific, social, and ethical considerations of this controversial field.